Pengaruh Play Therapy Dengan Media Boneka Tangan Dalam Bimbingan Kelompok Terhadap Sosio Emosional Siswa SMP Hang Tuah 1 Surabaya Di Masa Pandemi Covid-19 - Kholisah, Kholifatul Dwinur; Sutijono, Sutijono; Farid, Dimas Ardika Miftah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the effect of play therapy with hand puppet media in group guidance on the socio-emotional of students of SMP Hang Tuah 1 Surabaya during the Covid-19 pandemic. This type of research is pre-experimental using a quantitative approach. In this study design using a research design one group pre-test post-test design. The research subjects were 5 students who have low socio-emotional levels. Hypothesis testing used by researchers is the Wilcoxon signed ranks test. The results of this study indicate that there is an increase in the average socio-emotional score of students of SMP Hang Tuah 1 Surabaya from the mean pre-test 76.80 to the post-test mean value of 96.60 which means that play therapy with hand puppet media in group guidance affects socio-emotional. students (Asymp. Sig = 0.043; Asymp. Sig = 0.043 <α = 0.05). Based on the results of the study, it was proven that the use of play therapy with hand puppet media in group guidance had an effect on increasing students' socio-emotional.